APOE genotype, hippocampus, and cognitive markers of Alzheimer's disease in American Indians: Data from the Strong Heart Study. Issue 12 (10th February 2022) - Suchy‐Dicey, Astrid; Howard, Barbara; Longstreth Jr, WT; Reiman, Eric M.; Buchwald, Dedra
Abstract: Background: The apolipoprotein E ( APOE ) ε4 allele confers higher risk of neurodegeneration and Alzheimer's disease (AD), but differs by race/ethnicity. We examined this association in American Indians. Methods: The Strong Heart Study is a population‐based cohort of American Indians who were 64 to 95 years of age in 2010 to 2013. APOE ε4 status, brain imaging, and neuropsychological testing was collected in N = 811 individuals. Summary statistics, graphics, and generalized linear regressions—adjusted for sociodemographics, clinical features, and intracranial volume with bootstrap variance estimator—compared APOE ε4 carriers with non‐carriers. Results: APOE ε4 carriers comprised 22% of the population (0.7% homozygotes). Participants were mean 73 years, 67% female, and 54% had some college education. The majority were obese (>50%), hypertensive (>80%), and diabetic (>50%). Neither imaging findings nor multidomain cognitive testing showed any substantive differences between APOE ε4 carriers and non‐carriers. Conclusion: We found no evidence of neurodegenerative risk from APOE ε4 in American Indians. Additional studies are needed to examine potential protective features.